2013
DOI: 10.1016/j.janxdis.2013.01.006
|View full text |Cite
|
Sign up to set email alerts
|

Intolerance of uncertainty and negative metacognitive beliefs as transdiagnostic mediators of repetitive negative thinking in a clinical sample with anxiety disorders

Abstract: This study aimed to replicate and extend a hierarchical model of vulnerability to worry, with neuroticism and extraversion as higher-order factors and negative metacognitions and intolerance of uncertainty as second-order factors. The model also included a transdiagnostic measure of repetitive negative thinking (RNT) and depression symptoms as outcome variables to determine whether relationships would extend beyond worry, which has traditionally been studied within the context of generalized anxiety disorder (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
32
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(41 citation statements)
references
References 79 publications
8
32
1
Order By: Relevance
“…Most studies (81%) were descriptive in nature. Mechanistic constructs were more infrequent (19%), and causal transdiagnostic constructs were hardly ever reported (7%) and only during the most recent years (2017‐2018).…”
Section: Resultsmentioning
confidence: 99%
“…Most studies (81%) were descriptive in nature. Mechanistic constructs were more infrequent (19%), and causal transdiagnostic constructs were hardly ever reported (7%) and only during the most recent years (2017‐2018).…”
Section: Resultsmentioning
confidence: 99%
“…Bean & Groth-Marnat, in press) few have examined how personality may influence attitudes toward games. However, it is not unreasonable to suggest that high neuroticism and low openness may predict negative beliefs about games as such personality traits are typically connected with greater worrying (McEvoy & Mahoney, 2013) and difficulty adopting new technologies in job-related contexts (Minbashian, Earl, & Bright, 2013) or relating to different styles of media such as heavy metal (Swami et al, 2013).…”
Section: Beliefs About Media Effectsmentioning
confidence: 99%
“…A greater endorsement of negative metacognitive beliefs has been associated with anxiety (Davis & Valentier, 2000;McEvoy & Mahoney, 2013), depression (Papageorgiou & Wells, 2001) and obsessive compulsive disorder (Wells & Papageorgiou, 1998). In addition prospective cohort studies have found that higher levels of unhelpful metacognitive beliefs at baseline predict subsequent severity of anxiety and depression (Hjemdal, Stiles, & Wells, 2013;Papageorgiou & Wells, 2009;Yilmaz, Gencoz, & Wells, 2011).…”
Section: Introductionmentioning
confidence: 99%